The Effect Of Realistic Mathematics Education On Elementary School Students' Mathematical Problem-Solving Abilities - Susanto, Hendra; Diah Setiawati; Wiwin Apriani (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to examine the influence and the degree of effectiveness of Realistic Mathematics Education (RME) on the mathematical problem-solving abilities of elementary school students. Employing a quantitative approach, the research utilized an experimental method with a one-group pretest–posttest design. The participants consisted of fourth-grade students at State Elementary School Telaga Tujuh Langsa. Data were collected through problem-solving tests and analyzed using paired sample t-tests and the eta-squared effect size formula. The findings indicated a significant influence of RME on students’ problem-solving abilities, as evidenced by a tcount > ttable, which was 15.961 >1.753. Furthermore, the eta-squared coefficient was calculated at 0.944, suggesting a very high level of influence. These results demonstrate that RME is highly effective in enhancing the mathematical problem-solving skills of elementary school students